Animal welfare of Lacaune lambs weaned from artificial feeding - Moreno Manrique, María; Mínguez Balaguer, Carlos; Ibáñez Sanchis, Carla; González Clari, Marta; Villagrá García, Arantxa; Bueso Ródenas, Joel (Frontiers in Veterinary Science, 2024)
IntroductionNowadays, many dairy sheep farms opt for milk replacers after birth. Weaning lambs from milk replacers is expected to be a stressful situation.MethodsWith the aim of researching this practice on the animal behavior, body weight yields, and sanitary status of Lacaune lambs, 60 healthy animals from the same lambing house were employed. Lambs were housed in a pen and had ad libitum access to forage, compound feed, and milk replacers. During a 4 days preexperimental period in which all the animals were fed with milk replacers, behavior, hematologic parameters, body weight and seric and fecal stress indicators were recorded. Later, an experimental period took place in which 20 lambs remained in the same conditions. Another 20 lambs were kept in a separate pen in the same barn under the same conditions, but the artificial milk feeding was interrupted (weaning). The third 20 lambs were weaned and also rehoused in fattening pens. After 4 days, the variables previously recorded in the three groups during the pre-experimental period were recorded again.ResultsResults showed that change of location and change of feed can have different and synergic effects on the behavior of the lambs. Change of feed had not specifically different effect on body weight than change of location. In the other hand, weaning had no significative effects on hematologic parameters and seric and fecal stress indicators.DiscussionWeaning from artificial milk had significative effects on lambs weight and behavior. More research is needed to improve this ethical aspect in ovine production.